More conservative dentistry: clinical long-term results of direct composite resin restorations - Staehle, Hans Jörg; Wolff, Diana; Frese, Cornelia (Quintessence international, 2015)
Current treatment protocols and recent developments in composite resin technology allow for extended indication of direct composite resin restorations. This article presents clinical longterm observations of direct composite resin restorations indicated for primary and replacement therapy, repair restorations, direct crowns, and composite buildups for the correction of tooth form.
Gesehen am 09.08.2017